Hierarchical Superstructure of Plant Polyphenol and Arginine Surfactant for Long-Lasting and Target-Selective Antimicrobial Application - Shen, Yutan (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.